Three poets : Shamsur Rahman, Al Mahmud, Shaheed Quaderi - Rahman, Shamsur; Āla Māhamuda, 1936-; Quaderi, Shaheed; Rashid, M. Harunur (Poems from Bangladesh series., 1976)
Selected poems; includes introduction to the poets.